PERTUMBUHAN DAN HASIL TANAMAN SELEDRI (Apium graveolens L.) TERHADAP PEMBERIAN KOMBINASI PUPUK NPK DAN POC KULIT PISANG PADA TANAH GAMBUT - Findi Wahyuni Pratiwi; Rini Wilu Susana; Tatang Abdurrahman (Fakultas Pertanian, Universitas Janabadra, 2023)
The development of celery on peat soil is faced with various obstacles including the low availability of nutrients. Efforts to overcome these obstacles are by applying a combination of NPK fertilizer and banana peel liquid organic fertilizer. This study aims to determine the best combination of doses of NPK fertilizer and liquid organic fertilizer concentration of banana peels on the growth and yield of celery plants on peat soil. The research was conducted at the Research House of the Faculty of Agriculture, University of Tanjungpura from September 1 2022 to November 26 2022. The study used a Completely Randomized Design, consisting of 5 treatment levels with 5 replications consisting of 4 sample plants. The treatment consisted of P1 = NPK 600 kg/ha equivalent to 2.4 g/plant + liquid organic fertilizer of banana peel 10 ml/L, P2 = NPK 500 kg/ha equivalent to 2 g/plant + liquid organic fertilizer of banana peel 20 ml /L, P3 = NPK 400 kg/ha equivalent to 1.6 g/plant + liquid organic fertilizer of banana peel 30 ml/L, P4 = NPK 300 kg/ha equivalent to 1.2 g/plant + liquid organic fertilizer of banana peel 40 ml/L and P5 = NPK 200 kg/ha equivalent to 0.8 g/plant + liquid organic fertilizer of banana peel 50 ml/L. The results showed that the application of banana peel liquid organic fertilizer at higher concentrations could replace the use of NPK fertilizer.INTISARIPengembangan tanaman seledri pada tanah gambut dihadapkan pada berbagai kendala diantaranya ketersedian hara yang rendah. Upaya untuk mengatasi kendala tersebut adalah dengan pemberian kombinasi pupuk NPK dan POC kulit pisang. Penelitian ini bertujuan untuk mengetahui kombinasi dosis pupuk NPK dan konsentrasi POC kulit pisang yang terbaik terhadap pertumbuhan dan hasil tanaman seledri pada tanah gambut. Penelitian dilaksanakan di Rumah Penelitian Fakultas Pertanian Universitas Tanjungpura sejak tanggal 1 September 2022 sampai 26 November 2022. Penelitian menggunakan Rancangan Acak Lengkap, terdiri dari 5 taraf perlakuan dengan 5 ulangan yang terdiri dari 4 tanaman sampel. Perlakuan terdiri dari P1= NPK 600 kg/ha setara dengan 2,4 g/tanaman + POC Kulit Pisang 10 ml/L, P2= NPK 500 kg/ha setara dengan 2 g/tanaman + POC Kulit Pisang 20 ml/L, P3= NPK 400 kg/ha setara dengan 1,6 g/tanaman + POC Kulit Pisang 30 ml/L, P4= NPK 300 kg/ha setara dengan 1,2 g/tanaman + POC Kulit Pisang 40 ml/L dan P5= NPK 200 kg/ha setara dengan 0,8 g/tanaman + POC Kulit Pisang 50 ml/L). Hasil penelitian menunjukkan bahwa pemberian POC kulit pisang pada konsentrasi yang lebih tinggi dapat menggantikan pengunaan pupuk NPK.